2021
DOI: 10.1097/bsd.0000000000001291
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Preoperative Cervical Deformity Experience Similar Clinical Outcomes to Those Without Deformity Following 1–3 Level Anterior Cervical Decompression and Fusion

Abstract: Objective: The aim was to compare the outcomes of patients with incompletely corrected cervical deformity against those without deformity following short-segment anterior cervical decompression and fusion for clinically significant radiculopathy or myelopathy.Summary of Background Data: Cervical deformity has increasingly been recognized as a driver of disability and has been linked to worse patient-reported outcomes measures (PROMs) after surgery.Methods: Patients 18 years or above who underwent 1-3 level ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
(97 reference statements)
3
3
1
Order By: Relevance
“…[ 7 ] We did find a significant increase in C2-C7 SVA between preoperative and postoperative time points, which also supports previous studies. [ 5 7 22 ] Interestingly, our study was unable to detect differences between preoperative and intraoperative time points, suggesting intraoperative measurements may mask the expected change postoperatively. C2-C7 SVA is a marker for the head position in relation to the cervical spine, and changes in C2-C7 SVA may result from postural compensation to degenerative changes of the cervical spine.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[ 7 ] We did find a significant increase in C2-C7 SVA between preoperative and postoperative time points, which also supports previous studies. [ 5 7 22 ] Interestingly, our study was unable to detect differences between preoperative and intraoperative time points, suggesting intraoperative measurements may mask the expected change postoperatively. C2-C7 SVA is a marker for the head position in relation to the cervical spine, and changes in C2-C7 SVA may result from postural compensation to degenerative changes of the cervical spine.…”
Section: Discussionsupporting
confidence: 91%
“…Whether ACDF increases C2-C7 lordosis is controversial, as numerous studies have demonstrated statistically significant differences between preoperative and postoperative measurements, whereas others have not. [ 4 5 7 8 21 ] Our findings align with a similar study from our institution, which found no differences in C2-C7 lordosis in 230 patients who underwent ACDF. [ 7 ] We did find a significant increase in C2-C7 SVA between preoperative and postoperative time points, which also supports previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies have reported that C2–7 SVA > 4 cm is associated with worsened PROs after multilevel posterior cervical deformity surgery [ 29 ], and this criterion is part of the comprehensive cervical spine deformity classification system which was proposed by Ames et al [ 19 ] Although these studies certainly suggest that a C2–7 SVA of < 4 cm may be beneficial to achieve in those undergoing cervical deformity correction, they should not necessarily be interpreted as meaning that all patients with radiculopathy or myelopathy need to have a value < 4 cm to achieve an optimal outcome. By contrast, in a recent study by Karamian et al [ 30 ] of patients undergoing 1–3 level anterior cervical discectomy and fusion, those with a preoperative C2–7 SVA of > 4 cm actually had greater improvement in Neck Disability Index scores postoperatively versus those with a C2–7 SVA < 4 cm, even though the SVA values remained > 4 cm in the former group and < 4 cm in the latter. In other words, in patients with primarily radiculopathy or myelopathy, C2–7 SVA may not necessarily be a major driver of outcomes.…”
Section: Discussionmentioning
confidence: 74%